Obravnava bolnikov z arterijsko hipertenzijo - Farkaš-Lainščak, Jerneja (Zdravniški vestnik, 2008)
An association between arterial hypertension (AH) and risk for cardiovascular diseases (CVD) has been confirmed in many large scale epidemiological studies.Prevalence and control of AH can be improved wide both public health and individually tailored actions. These include lifestyle modifications and implementation of results in clinical practice. However, suboptimal managementof AH is a worldwide public health problem. In Slovenia, there is limited data on epidemiology and AH control. This review aimed to comprehensively summarize epidemiological studies of AH control and to discussmost frequent reasons for suboptimal management of AH Finally, two models on improvement of management of AH are presented and potential applications for Slovenia are discussed. Actions, for better management of AH need to be comprehensive. This includes active patient involvement in partnership with a doctor, implementation of clinical guidelines in clinical practice, and flexibility of health care system, in particular in primary care.
Keywords: arterijska hipertenzija; bolniki; Diagnosis; epidemiologija; Hipertenzija; Hypertension; Practice Guidelines; Praktična navodila; smernice; Therapy; zdravljenje; zdravstveno varstvo